Delayed Occurrence of Escherichia coli Subdural Empyema Following Head Injury in an Elderly Patient: A Case Report and Literature Review - Munusamy, Thangaraj; Dinesh, Shree Kumar (Journal of Neurological Surgery Reports, 2015)
Subdural empyema is a rare but serious intracranial infection that warrants prompt management to reduce morbidity and avoid mortality. However, clinical and radiologic features may be subtle or ambivalent. Thus a diagnosis of subdural empyema should not be discounted, especially in a patient with a history of head trauma. Treatment consists of surgery to establish bacteriologic identification and subsequently guide antibiotic therapy. Here we present a case of delayed Escherichia coli subdural empyema following a head injury in an elderly patient without significant risk factors. Computed tomography imaging was equivocal for subdural empyema. The patient underwent surgery and was treated with intravenous antibiotic therapy. Although initial improvement in the patient's clinical condition was observed, he eventually succumbed to nosocomial pneumonia. In this article, we discuss the presentation, diagnostic tools, and treatment options for subdural empyema with an emphasis on the challenges. The management conundrum that follows prompted us subsequently to review the literature.
Keywords: subdural empyema; head injury; antibiotic therapy; chronic subdural hematoma